2016
DOI: 10.1371/journal.pntd.0004629
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Regression Analysis in Schistosoma mansoni-Infected Individuals in the Sudan Reveals Unique Immunoepidemiological Profiles in Uninfected, egg+ and Non-egg+ Infected Individuals

Abstract: BackgroundIn the Sudan, Schistosoma mansoni infections are a major cause of morbidity in school-aged children and infection rates are associated with available clean water sources. During infection, immune responses pass through a Th1 followed by Th2 and Treg phases and patterns can relate to different stages of infection or immunity.MethodologyThis retrospective study evaluated immunoepidemiological aspects in 234 individuals (range 4–85 years old) from Kassala and Khartoum states in 2011. Systemic immune pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 49 publications
5
30
0
Order By: Relevance
“…In a further new supplementary regression analysis we combined data from the first publication [18] with the new immune data measured here. Pvalues of less than 0·05 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a further new supplementary regression analysis we combined data from the first publication [18] with the new immune data measured here. Pvalues of less than 0·05 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Next, epidemiological covariates [exposure, latrine, education, age (subgrouped), co-infection and gender], chemokine and SWA-Ig levels were included in a stepwise logistic regression with forward selection, as described previously [18], and results are shown in Table 2. This new data analysis revealed for the first time that SWAspecific IgG3 was significantly associated with infection per se , and additionally, SWA-specific IgG2 was associated with a Sm PCR + diagnostic state.…”
Section: Multivariable Regression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that IgM and IgE are extremely high in serum of infected population compared to uninfected population. It synoptically means that without the help of or release of IL-4, there will be no protection to fighting parasitic reinfection, and 2016 result of [20] arrived at the same conclusion with Nmorsi. Hence, measurement of immunoglobulin concentration can be used as indicators of heavy and acute infection of S. haematobium in our endemic localities.…”
Section: Overview Roles Of Interleukin 4 In Urinary Schistosomiasismentioning
confidence: 99%